Disclosure and concealment of sexual orientation and the mental health of non-gay-identified, behaviorally bisexual men - Schrimshaw, Eric W; Siegel, Karolynn; Downing, Martin J; Parsons, Jeffrey T (Journal of consulting and clinical psychology, 2013)
Although bisexual men report lower levels of mental health relative to gay men, few studies have examined the factors that contribute to bisexual men's mental health. Bisexual men are less likely to disclose, and more likely to conceal (i.e., a desire to hide), their sexual orientation than gay men. Theory suggests that this may adversely impact their mental health. This report examined the factors associated with disclosure and with concealment of sexual orientation, the association of disclosure and concealment with mental health, and the potential mediators (i.e., internalized homophobia, social support) of this association with mental health. An ethnically diverse sample of 203 non-gay-identified, behaviorally bisexual men who do not disclose their same-sex behavior to their female partners were recruited in New York City to complete a single set of self-report measures. Concealment was associated with higher income, a heterosexual identification, living with a wife or girlfriend, more frequent sex with women, and less frequent sex with men. Greater concealment, but not disclosure to friends and family, was significantly associated with lower levels of mental health. Multiple mediation analyses revealed that both internalized homophobia and general emotional support significantly mediated the association between concealment and mental health. The findings demonstrate that concealment and disclosure are independent constructs among bisexual men. Further, they suggest that interventions addressing concerns about concealment, emotional support, and internalized homophobia may be more beneficial for increasing the mental health of bisexual men than those focused on promoting disclosure.